Health investment over the life-cycle - Timothy J. Halliday; Hui He; Hao Zhang (Institute for the Study of Labor (IZA), 2009)
We study the evolution of health investment over the life-cycle by calibrating a model of endogenous health accumulation. The model is able to produce the decline in labor supply with age as well as the hump-shaped consumption profile. In both cases, health and health investment play a crucial role as the former encroaches upon healthy time and the latter crowds out non-medical expenditures as people age. Finally, we quantify the value of health as both an investment and a consumption good. We show that the investment motive is about three times higher than the consumption motive during the early 20s, but decreases over the life-cycle until it disappears at retirement. In contrast, the consumption motive increases with age and surpasses the investment motive during the mid 40s.
Keywords: I12; 330; Health investment; structural model; medical expenditures; Gesundheitsvorsorge; Lebenszyklus; Verbraucherausgaben; USA